2019
DOI: 10.2478/rjim-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

The neutrophil to lymphocyte ratio in heart failure: a comprehensive review

Abstract: Introduction. Heart failure (HF) and systemic inflammation are interdependent processes that continuously potentiate each other. Distinct pathophysiological pathways are activated, resulting in increased neutrophil count and reduced lymphocyte numbers, making the neutrophil to lymphocyte ratio (NLR) a potential indirect marker of severity. We conducted this comprehensive review to characterize the role of NLR in HF. Methods. We searched the PubMed (MEDLINE) database using the key words “neutrophil”, “lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 49 publications
(89 reference statements)
1
38
0
2
Order By: Relevance
“…In a study on HF patients performed by Yan et al it was shown that high NLR is associated with a higher rate of major cardiovascular events in elderly patients with HF [ 25 ]. Moreover, the prognostic role of increased NLR in HF patients was confirmed by Delcea et al in a comprehensive review [ 26 ]. We found a significant difference in NLR and PLR in HFrEF patients, but in the Cox regression the difference was not significant.…”
Section: Discussionmentioning
confidence: 89%
“…In a study on HF patients performed by Yan et al it was shown that high NLR is associated with a higher rate of major cardiovascular events in elderly patients with HF [ 25 ]. Moreover, the prognostic role of increased NLR in HF patients was confirmed by Delcea et al in a comprehensive review [ 26 ]. We found a significant difference in NLR and PLR in HFrEF patients, but in the Cox regression the difference was not significant.…”
Section: Discussionmentioning
confidence: 89%
“…NLR is a reflection of physiological stress and a marker of the interaction between different immune pathways. NLR was shown to be an independent predictor of in-hospital mortality for many cardiovascular, neurovascular, and intensive-care conditions [17,18], and high NLR values can be observed in very heterogenous diseases and conditions. This is why NLR is generally considered a marker of physiologic stress among hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed that the mean CRP value was significantly higher in MVP patients compared to the control group, as expected. In reviewing the literature, we found a strong association between NLR and inflammation in cardiac and non-cardiac disorders 8,[29][30][31] . Several reports have shown that higher NLR levels are linked with increased inflammation in many cardiac diseases, such as coronary artery disease 9 and rheumatic valvular disease 32 .…”
Section: Discussionmentioning
confidence: 98%